(untitled) - FIALOVÁ, Irena; PAVLÍČEK, Jiří (Trends in education, 2008)
Faculty of Education Charles University in Prague and Faculty of Education Ostrava University co-operate on the SOCRATES program Socrates Project Gender awareness in media education. The purpose of this project is: in Teacher Education new media (ICT) are used with competence and combined with gender aspects.
Keywords: Gender sensitive education; diagnostic tool; innovative learning environment.